An overview of deterministic and probabilistic analytical approaches for non-linear seismic risk assessment of structures - Ayman, Mohammad Mansour; Al Biajawi, Mohammad Ismail Yousef (Penerbit UTHM, 2022)
Performance-based earthquake engineering (PBEE) is a framework that seeks to improve decision-making for seismic risk mitigation through assessment and design methods featuring performance metrics that meet the diverse needs and objectives of owners/users and society. The selection of seismic design analysis approach depends on several factors such as the size and layout of the structure, design objectives, seismic design category, and the value of the structure. Generally, analysis methods can be categorized into two major groups: static and dynamic analysis, both of which are possible to be conducted as linear or nonlinear analysis. This paper presents an overview of the procedures of the nonlinear analysis methods, namely the nonlinear static analysis (NL-SA) and nonlinear dynamic analysis (NL-DA), in addition to the development of fragility curves for a probabilistic seismic risk assessment.